Utilizing physical educators to monitor muscular strength and neuromuscular control among children with varied recess time - G. Kate Webb; Yan Zhang; Deborah J. Rhea (Frontiers in Sports and Active Living)
IntroductionInactivity levels among children are climbing at alarming rates, leading to a lack of physical activities that produce muscular strength (MusS) development, which in turn creates effective neuromuscular control (NC) development. Developing appropriate MusS during childhood decreases the chances of physical injuries and many chronic diseases such as type II diabetes and cancer, which leads to healthier, active future adults. The purpose of this study was to utilize the physical education setting to examine MusS and NC factors in the Fall and Spring (Time 1 to Time 2) of one school year in a predominately Hispanic sample of second-grade children who received 60 min or 20 min of daily recess.MethodsThis quasi-experimental pre-test/post-test study administered four MusS tests and one NC test to District 1 (N = 59) which received 60 min of recess daily (intervention), and District 2 (N = 49) which received one 20 min daily recess (control). ANCOVAs were run for group differences at Time 2 while controlling for Time 1.ResultsIntervention children significantly outperformed control children on the single leg 3-hop muscular strength test F(1,105) = 13.1, p < .001, n2 = .05, and the neuromuscular control side-step test F(1,105) = 4.77, p = .03, n2 = .04. Between group ANCOVAs controlling for body fat percentages showed the single leg 3-hop test remained significant between groups F(1,91) = 23.5, p < .001, n2 = .09.DiscussionIncreased recess was shown to aid in improved lower body muscular strength and neuromuscular control among second grade children, even when controlling for body fat percentages. As 70% of American children are not participating in the recommended daily activity guidelines, and roughly 20% of American children are overweight, exploring movement opportunities for children and efficient means of monitoring MusS and NC is pivotal to future health and movement functions of children.